Plasticity of Executive Control through Task Switching Training in Adolescents - Zinke, Katharina; Einert, Manuela; Pfennig, Lydia; Kliegel, Matthias (Frontiers in Human Neuroscience, 2012)
Research has shown that cognitive training can enhance performance in executive control tasks. Current study was designed to explore whether executive control can also be trained in adolescents, what particular aspects of executive control may underlie training and transfer effects, and whether acute bouts of exercise directly prior to cognitive training enhance training effects. For that purpose, a task switching training was employed that has been shown to be effective in other age groups. A group of adolescents (10-14 years, n = 20) that received a three-week TS training was compared to a group (n = 20) that received the same TS training but who exercised on a stationary bike before each training session. Additionally, a no-contact and an exercise-only control group were included (both ns = 20). Analyses indicated that both training groups significantly reduced their switching costs over the course of the training sessions and also reduced their mixing costs in a near transfer task. The reduction in mixing costs in the near transfer task was larger in the trained groups than in the non-trained control groups. Far transfer of cognitive training was limited to a choice reaction time task and a tendency for faster reaction times in an updating task. Findings indicate that executive control can be enhanced in adolescents through training and that updating may be of particular relevance for the effects of task switching training.